Proyecto de factibilidad para la producción de la especie menta y su comercialización en la ciudad de Loja - Angamarca Michay, Mary Catalina (2024)
The Curricular Integration work titled "Feasibility Project for the Production and Commercialization of Mint in Loja city" aims to determine the technical, economic, and financial viability of creating a company dedicated to the production and commercialization of mint. For this purpose, a market study was conducted, revealing that approximately 85% of families in Loja city consume the mentioned species. Therefore, in the technical study, based on macro and micro location, the production site was located at Chuquiribamba, in the Loja province. According to the organizational study, the hierarchical order was defined along with the respective functions of the work team. From the economic-financial study, it was determined that the amount required for the initial investment was $11,147.70, with financing through a bank loan from Ban Ecuador amounting to $10,000.00, representing 89.75%, and 10.25% financed with own capital, amounting to $1,147.70. Regarding the financial evaluation indicators, the Net Present Value was $17,209.29, the Internal Rate of Return was 70.99%, the Cost-Benefit Ratio was 1.82, and the capital recovery was estimated at 1 year, 3 months, and 4 days. Finally, the Sensitivity Analysis showed that the project could tolerate a 22% increase in costs and a 40% decrease in income. Consequently, the mentioned project has proven to be viable and profitable in all its parameters, and therefore its implementation is feasible.